Echocardiography Features in Patient Rheumatic Mitral Stenosis - Dwigustiningrum, Nur Kaputrin; Rahimah, Anna Fuji; Karolina, Wella; Martini, Henny (Heart Science Journal, 2024)
Rheumatic mitral stenosis (RMS) is a progressive valvular heart disease that can lead to significant morbidity and mortality, especially in developing countries. Echocardiography plays a crucial role in the diagnosis, assessment, and management of patients with RMS. This study aims to review the utility echocardiography feature in patient RMS. We discuss the key echocardiographic parameters used for assessment and severity of RMS, and associated valvular abnormalities. Additionally, we explore the role of multimodality imaging, such as transesophageal echocardiography in enhancing the diagnostic accuracy and therapeutic decision-making in RMS. A thorough understanding of echocardiographic findings in RMS is essential for clinicians involved in the care of these patients, as it aids in risk stratification, treatment planning, and monitoring of disease progression. Integrating echocardiography is a widely used non-invasive method for comprehensive assessment, monitoring disease progression and evaluating treatment efficacy, ensuring optimal management for patient with RMS.